When digital technology distracts: Impact on cognitive load and work productivity in Generation Z - Bagus M. Fatah Kertarajasa; Imas Soemaryani (Jurnal Fokus Manajemen Bisnis, 2026)
This study examines how digital technology distraction affects employees’ cognitive load and work productivity, focusing on Generation Z employees at Telkom Indonesia Company within a hybrid work setting. Grounded in cognitive load theory, the research evaluates whether frequent notifications, multitasking, and overlapping digital activities heighten cognitive strain and reduce performance. Using a quantitative approach, data were collected from 108 respondents via online surveys, and purposive sampling was used to ensure a representative sample. The proposed model was analyzed using SmartPLS for the structural equation model with partial least squares, and process model 5 was applied to test mediation effects using SPSS. The findings show that digital technology distraction significantly increases cognitive load, and higher cognitive load subsequently decreases work productivity. In addition, digital technology distraction also has a significant direct adverse effect on work productivity. Mediation results indicate partial mediation, confirming that cognitive load is a central mechanism through which digital distractions translate into productivity loss. The study advances workplace digital-distraction literature by validating cognitive load theory in a real-world hybrid work environment and by providing evidence specific to Generation Z employees, who face high digital exposure at work. In practice, the findings highlight the need for digital exposure management and attention regulation strategies to sustain Generation Z performance in hybrid workplaces.